2023
DOI: 10.3390/ijerph20010878
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Disempowering Climates on Teaching Intention in (Physical Education) Initial Teacher Education

Abstract: Previous research has looked at the positive consequences generated by teacher-generated climates on the motivational experiences of pre-service teachers. However, there is scant research focusing on the adverse motivational consequences that affect the perceptions of future teachers during the training process. The objective of this study was to explore the dark side of Duda’s multidimensional conceptualization, its influence on academic engagement, and the intention of pre-service teachers to be educators. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 55 publications
1
6
1
Order By: Relevance
“…Contrasted with our hypotheses, pre-service PE teachers’ competence satisfaction positively predicted their controlled motivation. This result differed from Kaplan and Madjar’s (2017) study that revealed that both variables were unrelated in pre-service generalist teachers, while it was partially aligned with the López-García et al’s (2023) research, given that a positive association was found from pre-service generalist teachers’ need satisfaction to their controlled motivation. This finding makes us suggest that when pre-service PE teachers feel their competence as satisfied, they could also have controlled reasons toward their initial teacher education program.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Contrasted with our hypotheses, pre-service PE teachers’ competence satisfaction positively predicted their controlled motivation. This result differed from Kaplan and Madjar’s (2017) study that revealed that both variables were unrelated in pre-service generalist teachers, while it was partially aligned with the López-García et al’s (2023) research, given that a positive association was found from pre-service generalist teachers’ need satisfaction to their controlled motivation. This finding makes us suggest that when pre-service PE teachers feel their competence as satisfied, they could also have controlled reasons toward their initial teacher education program.…”
Section: Discussioncontrasting
confidence: 91%
“…Indeed, it is thought that controlled motivation might be an effective way to foster short-term academic engagement among pre-service PE teachers; however, there is a need for longitudinal studies to analyze if the effects of controlled motivation on academic engagement would be maintained throughout initial PE teacher education. Moreover, and following López-García et al’s (2023) research, our results also displayed a negative association of amotivation on academic engagement. This could be explained in that when pre-service PE teachers with levels of futility, inefficacy, undervaluation, and disinterest in their initial teacher education program, they will be prone to have a lower academic engagement with their teaching career.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations